(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Cervical spondylosis myelopathy (CSM) is a common cause of disability in older persons. Because spondylosis is a universal finding as the patients aged. Objective: To assess the demographic and management of cervical spondylosis in a sample of Iraqi patients. Methods: This is a prospective clinical study, carried out over the period from January 2013 to December 2014, and included 25 patients with cervical spondylosis myeloradiculopathy referred for surgical intervention in Neurosurgical Department in the Al-Imamein Al-Kadhimein Medical City. General examination and full neurological assessment were performed, as well as relevant investigations, particularly; radiological assessments. All of the patients were subjected to surgery, with 17 patients (68%) were treated with laminectomy and foraminotomy, while the remaining 8 patients (32%) were treated with laminectomy only. Results: They were 14 males and 11 females, slightly affects males more than females, aged 38 to 82 years it is more common in 5th and 6th decades of life, and in rural than urban areas. Myeloradiculopathic features were the most common presenting ones with C5-C7, which were the most affected levels. General examination and full neurological assessment were performed, as well as relevant investigations, particularly; radiological assessments. All of the patients were subjected to surgery, with 17 patients (68%) were treated with laminectomy and foraminotomy, while the remaining 8 patients (32%) were treated with laminectomy only. More than half of the patients were showed slight improvement in their complaints, while significant improvement occurred in more than 28 % of patients. Despite that, 20% of patients showed no improvement in their symptomatology, however; no reported deterioration was noticed in the study. Conclusion: Myeloradiculopathic feature were the most common presenting features with C5-C7 was the most level affected. Laminectomy with foraminotomy was surgery of choice in tow third of patients, with remaining one third underwent laminectomy only. Keywords: Cervical spondylosis, spinal cord compression Citation: Jaizany AJA, Nema IS, Hassan YM. Assessment of spinal cord compression in patients with cervical spondylosis, a clinical prospective study of 25 patients. Iraqi JMS. 2018; 16(2): 152-158. doi: 10.22578/IJMS.16.2.6